Severe Bilateral Hyperkeratosis of the Nipples and Areolae: A Case Report and Literature Review - Wei, Jiaying; Li, Qingshu; Wu, He; Yin, Xuedong; Ren, Guosheng (Frontiers in Medicine, 2022)
Importance Hyperkeratosis of the nipple and areola (HNA) is a rare skin disease with unknown etiology. Some patients are misdiagnosed or never diagnosed, especially during the early stage of this disease. Besides, the mechanism involving in the development of HNA is still unknown and the genomic alteration had not been reported anywhere. Objective To describe the main changes of histopathology and genomics in HNA. Design, Setting, and Participant A 26-year-old female with bilateral HNA was diagnosed at the first affiliated hospital of Chongqing Medical University. The disease-relevant information including a brief medical history, laboratory examinations, and treatment was collected. Main Outcomes and Measures The biopsy specimens harvested from the lesions were further used for histopathological examination and RNA-sequencing. Results No obvious abnormalities were found in laboratory tests examinations such as hormone testing for estrogen, progesterone or prolactin. The typical papillomatous skin with orthokeratotic hyperkeratosis and numerous infiltrating lymphocytes was detected through histopathological examination. The results from genomic analysis showed that the molecular expression between HNA and normal nipple and areola (NNA) was obviously different. However, no significant difference was found in the bilateral lesions. In addition, the immune-related cell signaling pathways was overactivated in HNA when compared to the control one. Conclusion and Relevance We present a young female patient with bilateral and severe HNA, in which typical symptoms, clinical features and histopathological alteration were described. The presentation of this rare case can make physicians more conscious of HNA. The possible mechanism involving in the development of HNA could be explained by the infiltration of a large number of lymphocytes revealed by histopathological examination and the dysfunction of cell signaling pathways and local immune system identified by genomic analysis. These findings suggests that anti-immune therapy like steroid treatment may be one of effective treatments applied to the patients with HNA disease at early stage.